2017
DOI: 10.1152/jn.00270.2017
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of long-term potentiation among identified inhibitory inputs to dopamine neurons

Abstract: The in vivo firing pattern of ventral tegmental area (VTA) dopamine neurons is controlled by GABA afferents originating primarily from the nucleus accumbens (NAc), rostromedial tegmental nucleus (RMTg), and local GABA neurons within the VTA. Although different forms of plasticity have been observed from GABA inputs to VTA dopamine neurons, one dependent on cyclic GMP synthesis and the other on adenylyl cyclase activation, it is unknown whether plasticity is differentially expressed in each. Using an optogeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 51 publications
3
27
0
Order By: Relevance
“…Furthermore, although synapses arising from VTA GABA neurons did exhibit reliable LTP, it was of smaller magnitude than in our previous studies utilizing electrical stimulation (Nugent et al , 2007, 2009; Niehaus et al , 2010; Graziane et al , 2013; Polter et al , 2014, 2017). Notably, our data are consistent with a recent report using a similar approach, both with respect to the circuit specificity and magnitude of LTP GABA (Simmons et al , 2017). These authors also reported that optically activated nucleus accumbens GABAergic inputs exhibit LTP GABA as well (Simmons et al , 2017).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore, although synapses arising from VTA GABA neurons did exhibit reliable LTP, it was of smaller magnitude than in our previous studies utilizing electrical stimulation (Nugent et al , 2007, 2009; Niehaus et al , 2010; Graziane et al , 2013; Polter et al , 2014, 2017). Notably, our data are consistent with a recent report using a similar approach, both with respect to the circuit specificity and magnitude of LTP GABA (Simmons et al , 2017). These authors also reported that optically activated nucleus accumbens GABAergic inputs exhibit LTP GABA as well (Simmons et al , 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Dopamine neurons are relatively depolarized basally and are spontaneously active both in vivo and in brain slices. GABA A R synapses interrupt dopaminergic cell firing both by hyperpolarization and by increasing conductance (Paladini et al , 1999a; Paladini et al , 1999b; Tan et al , 2012; Van Zessen et al , 2012), reducing the firing rate of dopamine neurons as shown in both pharmacological (Johnson & North, 1992; Suaud-Chagny et al , 1992; Paladini et al , 1999b) and optogenetic studies (Tan et al, 2012; Van Zessen et al, 2012; Simmons et al, 2017). Inhibitory synapses in the VTA are also dynamically regulated by experience.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Theta frequency stimulation induces selective LTP of GABA A receptor-mediated synaptic responses that involves activation of GABA B and glutamate type I/II metabotropic receptors in hippocampus (Patenaude et al 2003). GABA neurons in the ventral tegmental area (VTA) and accumbal GABAergic afferents also exhibit LTP after high frequency stimulation (Nugent et al 2007;Simmons et al 2017). However, much less is known about GABAergic LTP.…”
Section: Ltp Measured In Vitromentioning
confidence: 99%
“…() isolate and differentiate two of the major sources of inhibition arriving at dopamine neurons: The GABA‐releasing terminals from local GABA interneurons within the VTA, and from a region at the caudal tail of the VTA, termed the rostromedial tegmental nucleus (RMTg). The authors demonstrate that local VTA‐ and RMTg‐originating terminals define distinct channels of inhibition that possess unique spatial distributions, synaptic properties and capacities for long‐ and short‐term plasticity (see also Simmons et al ., ). Most intriguingly, the authors report two key properties of RMTg GABA‐releasing terminals: (i) They fail to express a unique form of long‐term potentiation previously characterized at VTA GABAergic terminals (i.e., LTP GABA ); and (ii) they corelease the neurotransmitter glycine.…”
mentioning
confidence: 97%